Khejri: A wonder tree for nutritional value - Meena, M L; Kumari, Nidhi; Kundu, M S (Indian Horticulture, 2023)
Khejri (Prosopis cineraria (L.) Marbride) is an important component of farming system and plays a significant role in the economy of Indian desert. Belonging to sub family Mimosoidae Fabaceae (Leguminoceae) family, the tree is found growing in arid and semi-arid parts of Rajasthan, Gujarat, Haryana, Punjab, Delhi and some parts of southern India. Its highly nutritious leaves constitute important source of fodder for livestock while nutritious pods are valued as vegetable for human beings. The immature pods are used as vegetables both fresh as well as after dehydration, while ripe dried pods can be powdered and used in the preparation of bakery items such as biscuits and cookies. The Khejri tree plays a vital role in maintaining the ecosystem of the dreary Thar region because of its ability to survive in such tough conditions and the different ways in which it can be used by the farmers. Monetary advantage obtained through cultivation of Khejri by adopting improved production technologies can be very well assessed through comparison between other plants and crops on the average yield, resources/inputs used and prevailing price of inputs and produce.